Leading forward : successful public leadership amidst complexity, chaos, and change - Flanagan, Tim A., 1955- (Jossey-Bass & Pfeiffer Imprints, Wiley, 2014)
Explains the four dimensions of effective leadership for leaders in the public sphere There is a wealth of advice available for corporate leaders, but little in the way of leadership guidance for those in government agencies. Leading Forward fills that gap by providing a development framework and assessment tool based on the four dimensions of effective leadership-empowerment, fairness, leaders, and supervisors. These four dimensions are critical competencies that leaders must develop in order to succeed now and in the future. Based on years of working with agency leaders at all levels of gove.